THE ROLE OF THE PRINCIPAL IN STRENGTHENING SCHOOLBASED MANAGEMENT (SBM) IN PUBLIC AND PRIVATE HIGH SCHOOL - Sakti Andayani (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
School-Based Management (SBM) demands effective leadership and organizational capacity for school autonomy to impact quality improvement. This study aims to analyze the role of principals in strengthening SBM in public high schools and compare instructional leadership practices and organizational capacity across school types. The research approach used a descriptive literature study design; data were collected from books, scientific articles, regulations, and reports that were analyzed critically and thematically. The results indicate that public high school principals are generally more mature in setting strategic goals, using data for evidence-based planning, implementing systematic academic supervision, and building a collaborative culture; while many private high schools especially medium and small experienced limitations in capacity, data, training, networking, and monitoring and evaluation mechanisms. The findings also emphasize the role of principals as capacity builders who mobilize resources and strengthen coordination. The discussion links the results to the literature on instructional leadership and SBM and highlights contextual barriers that influence implementation. This study addresses the research objectives by uncovering similarities and differences in leadership and organizational capacity-enhancing factors. It also recommends strengthening data-based training, developing monitoring and evaluation systems, and expanding partnerships as policy measures. These recommendations are expected to support more evidence-based, participatory, and sustainable SBM practices, thereby significantly improving the quality of learning in high schools